Ecotourism of the Lake Tisza - Remenyik Bulcsú; Dávid Lóránt (PoliPrint Kft., 2010)
Abstract. The present study has a double aim: partly to introduce some details of a Small Project realised in the eastern part of the Hungarian-Slovakian border and supported by the Phare CBC programme, and partly to give a brief analysis of the implementation of the Euroregional endeavours taking place in the border region – primarily from the aspect of tourism. It shall get a special role since the WTO designated the year 2002 as the year of ecotourism.One of the basic preconditions of the accession to the European Union is the creation and maintenance of good neighbourhood relations. The wide-scale development of the cross-border co-operations could be one of its forms of implementation which are to be carried out by the Euroregions.

Jelen tanulmány kettős céllal született: egyrészről a Phare CBC program által támogatott, és a magyar-szlovák határ keleti részén megvalósuló kisprojekt néhány részletét hivatott bemutatni, másfelől röviden elemezzük a határ menti területeket érintő euroregionális törekvések megvalósítását – elsősorban turisztikai szempontból. Ennek azért kell különös fontossággal bírnia, mivel a WTO a 2002-es évet az ökoturizmus évének nyilvánította. Az Európai Unióba való belépés egyik alapfeltétele a szomszédos országokkal való jó viszony kialakítása és fenntartása. A határokon átnyúló együttműködések széleskörű fejlesztése egyike lehet az Eurorégió által végrehajtandó feladatoknak.
https://epa.oszk.hu/01600/01626/00005/pdf/EPA01626_Acta_Beregsasiensis_2010_3.pdf?fbclid=IwAR2uhR2BlApYW5vWk0bKdZDkPr1-H2eiZ0fGQp7EK71Tas-Qm1RlapNhAp4
https://opac3.brff.monguz.hu:443/hu/record/-/record/135888
Keywords: ecotourism; Lake Tisza; hungarian tourism